Odpowiedzi

2010-01-24T01:58:48+01:00
I Temat:
zad.1) (2x+4)²=4x²+16x+16=4(x²+4x+4)
zad.2) (4-3√2)²=16-24√2+18=34-24√2=2(17-12√2)
zad.3) (x+1)(x-1)+(x+2)(x-2)-(x+3)(x-3)=x²-1+x²-4-x²+9=x²+4
x=√3
x²+4=(√3)²+4=3+4=7
zad.4) (√2-√6)(√2+√6)=2-6=-4
zad.5) a)1/√15*√15/√15=√15/15
b) 1/2-√3*2+√3/2+√3=2+√3/4-3=2+√3/1=2+√3
zad.6) (3-√3)³=27-27√3+27-3√3=54-30√3

IITemat:
zad.1) a) 2⁻²/3⁻³*(4/9)²=(1/2)²/(1/3)³*16/81=1/4*9*16/81=4/9
b) 6⁰+0⁶/6⁻¹+(4⁶-16³)=1+0/1/6+(4⁶-(4²)³)=1*6-(4⁶-4⁶)=6
zad.2) a) ((1/2)³)⁻³:16²=(1/2)⁻⁹:16²=2⁹:(2⁴)²=2⁹:2⁸=2¹=2
b) (1/64)⁻³*8⁻³/2⁵=64³*((2³)⁻³/2⁵=(2⁶)³*2⁻⁹/2⁵=2¹⁸*2⁻¹⁴=2⁴=16
zad.3) (-2√3)⁻³=(-1/2√3)³=-1/24√3*√3/√3=-√3/72

III Temat:
zad.1) a) (3,4*10⁷)*(4,5*10⁻⁵)=34000000*0,000045=1530
b) (3,3*10⁻¹²)*(1,2*10⁴)/4*10⁻¹⁸=10⁻¹²⁺¹⁸⁺⁴*3,3*1,2:4=10¹⁰*0,99